Arc‐parallel extrusion of the Timor sector of the Banda arc‐continent collision. Issue 3 (15th June 2013) - Duffy, Brendan; Quigley, Mark; Harris, Ron; Ring, Uwe
Abstract [1] Structural studies of synorogenic basins in Timor using field and remote sensing techniques provide new structural and geomorphic evidence for syn‐collisional extension in the converging plate boundary zone between the Australian Plate and Banda Arc. Fault mapping and kinematic analysis at scales ranging from outcrop (<1 m2) to the dimensions of the active orogen in East Timor ( 100 km2) identify a predominance of NW‐SE oriented dextral‐normal faults and NE‐SW oriented sinistral‐normal faults that collectively bound large (5–20 km2) bedrock massifs throughout the island. These fault systems intersect at non‐Andersonian conjugate angles of approximately 120° and accommodate an estimated 20 km of NE‐directed extension across the Timor orogen based on reconstructions of fault‐dismembered massifs. Major orogen‐parallel ENE‐oriented faults on the northern and southern sides of Timor exhibit normal‐sinistral and normal‐dextral kinematics, respectively. The overall pattern of deformation is one of lateral crustal extrusion sub‐parallel to the Banda Arc. Stratigraphic relationships suggest that extrusion began prior to 5.5 Ma, before pronounced rapid uplift of the orogen. We link this to progressive coupling of the fore‐arc to an underthrust plateau on the Australian Plate and subduction of its ocean crust. Our results enable us to track the structural evolution of the upper crust during dramatic plate‐boundary reorganizations accompanying the transition from subduction to collision. The deformation structures that we document suggest that both upper and lower plate deformation during incipient island arc‐continent collision was largely controlled by the geometry and topography of the lower plate.